(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article examines the possibilities for expanding cash flow management in commercial banks in New Uzbekistan under conditions of economic liberalization and financial sector transformation. The study highlights the role of modern liquidity management tools, digital banking technologies, and risk-based supervision in improving the efficiency of bank cash flows. Special attention is paid to recent legal and regulatory reforms, including updates to the Law of the Republic of Uzbekistan “On Banks and Banking Activity”, the Law “On the Central Bank of the Republic of Uzbekistan”, and new prudential regulations aligned with Basel III standards. The article analyzes how these reforms strengthen transparency, capital adequacy, and liquidity coverage ratios. Empirical and analytical methods are used to assess the impact of regulatory changes on short-term and long-term cash flow planning. The research also considers the growing importance of fintech solutions and real-time payment systems. The findings demonstrate that effective cash flow management enhances financial stability and credit activity. The article concludes with policy recommendations aimed at deepening reforms and increasing the resilience of commercial banks in New Uzbekistan.